2022
DOI: 10.3389/fgene.2022.708003
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Model for Predicting Tumor Mutation Burden and Tumor-Infiltrating Immune Cells in Bladder Urothelial Carcinoma

Abstract: Tremendous progress has been made in development of immunotherapeutic approaches for treatment of bladder urothelial carcinoma (BLCA). However, efficacy and safety of these approaches remain unsatisfactory, necessitating further investigations for identification of indicators for predicting prognosis and efficacy. In this study, we downloaded transcriptomic and clinical data of BLCA patients from The Cancer Genome Atlas (TCGA) database, and identified differentially expressed genes (DEGs) between tumor and nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Tumor-infiltrating T lymphocytes (TILs) represent a heterogeneous cell subpopulation within the TME ( 12 , 25 ). They exhibit significant plasticity and are associated with patient survival and therapeutic response in UC, making them a critical focus for distinguishing UTUC and BLCA.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor-infiltrating T lymphocytes (TILs) represent a heterogeneous cell subpopulation within the TME ( 12 , 25 ). They exhibit significant plasticity and are associated with patient survival and therapeutic response in UC, making them a critical focus for distinguishing UTUC and BLCA.…”
Section: Resultsmentioning
confidence: 99%
“…TMB, the total number of mutations in each coding region of the tumor genome, can be used to predict ICI efficacy ( 28 ). Interestingly, a significantly longer survival period was observed in the high-TMB group in comparison with the low-TMB group, suggesting that TMB is related to the prognosis of BLCA, and it has emerged as a useful biomarker for multiple cancer types to identify patients who may benefit from immunotherapy ( 29 , 30 ). On the other hand, a study has shown that MSI, independent of tumor histology and completely dependent on tumor gene composition, is a pan-cancer biomarker for predicting immunotherapy response ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, PCOLCE2 remains to be validated in vivo and in vitro for its specific mechanism in the EMT process of COAD. SCG2 has been identified as a prognostic biomarker associated with immune infiltration in CRC (41,42), bladder cancer (43,44), breast cancer (45), and lung adenocarcinoma (46). Wet assays revealed that SCG2 is lowly expressed in CRC, and inhibits the growth and angiogenesis of CRC cells by promoting the degradation of HIF-1α (47).…”
Section: Discussionmentioning
confidence: 99%